Information Retrieval Technology Asia Information Retrieval Symposium, AIRS 2004, Beijing, China, October 18-20, 2004. Revised Selected Papers - Myaeng, Sung Hyon; Zhou, Ming; Wong, Kam-Fai; Zhang, Hong-Jiang (Information Systems and Applications, incl. Internet/Web, and HCI, 2005)
TheAsiaInformationRetrievalSymposium(AIRS)wasestablishedbytheAsian information retrieval community after the successful series of Information - trieval with Asian Languages (IRAL) workshops held in six di?erent locations in Asia, starting from 1996. While the IRAL workshops had their focus on inf- mation retrieval problems involving Asian languages, AIRS covers a wider scope of applications, systems, technologies and theory aspects of information retrieval in text, audio, image, video and multimedia data. This extension of the scope re?ects and fosters increasing research activities in information retrieval in this region and the growing need for collaborations across subdisciplines. We are very pleased to report that we saw a sharp increase in the number of submissions and their quality, compared to the IRAL workshops. We received 106papersfromninecountriesinAsiaandNorthAmerica,fromwhich28papers (26%) were presented in oral sessions and 38 papers in poster sessions (36%). It was a great challenge for the Program Committee to select the best among the excellent papers. The low acceptance rates witness the success of this year's conference. After a long discussion between the AIRS 2004 Steering Committee and Springer, the publisher agreed to publish our proceedings in the Lecture Notes in Computer Science (LNCS) series, which is SCI-indexed. We feel that this strongly attests to the excellent quality of the papers.